Forecast of the morphology and occurrence conditions of complex chromite ore bodies (on example of Labogeyskoe-2 site, Polar Urals) - T. P. Morozova; E. V. Karelina; V. E. Markov (Известия высших учебных заведений: Геология и разведка, 2022)
Background. Chromium ores are confined to stratified massifs of basic and ultra-basic composition. The Voikaro-Sinyinsky massif is part of the main hyperbasite belt of the Urals. Inside the hyperbasites of this massif, at the boundaries of tectonic flakes in particular, ultra-basic metamorphites are developed, constituting the zones of sharply variable thickness. During survey routes, a mechanical halo of scattering of ore fragments was found. When studying the ore stockpile, ditches opened the Labogeyskoe-2 chromite ore body, which belongs to the Pogureysky block of the Voikaro-Sinyinsky massif. In the ore occurrence area, harzburgites are predominantly developed with thin striped dunite aggregates in a small volume and individual dunite bodies of low thickness. Chromium ores are densely impregnated, medium- to coarse-grained. The amount of chromospinelides in the composition of ores сonstitutes 90—95%, the serpentine of irregular shape as well as the relics of olivine and emerald-green uvorovite grains, along with the single grains of pyrrhotite and magnetite are found in the interstitia (2—5%). Ores are massive, often cataclazed. The experience of studying this ore occurrence can serve as an analogue for a more effective study of similar ore occurrences. Aim. Evaluation of the Labogeyskoye-2 ore occurrence for the application of the information obtained and methods of its study in the study of a similar Levopayersk ore body, which will help save time and finances in the design and more efficient exploration.Materials and methods. During the filming routes, a mechanical halo of scattering of ore fragments was detected. During the study of the ore collapse in 1966, the KM22—KM25 ditches were passed and the Labogeyskoye-2 chromite ore body was uncovered by the KM24 ditch. In 2013, during geological exploration at Labogeyskoye-2, 3 ditches (K50—K52) were passed and detailed gravimagnetic studies of Institute of Mineralogy, Geochemistry and Crystal Chemistry of Rare Elements in 2011—2012 were performed.Results. The Levopayerskoe ore body is probably the closest analogue of the Labogeyskoye-2 ore occurrence among the 24 ore occurrences, for which geological plans and calculation sections were compiled based on the results of mining and drilling operations.Conclusions. The closest analogue of the Labogeyskoye-2 ore occurrence is probably the Levopayerskoye ore body. Therefore, further geological and exploration work at the Labogeyskoe-2 site should be carried out taking into account the conditions of occurrence of the similar Levopayerskoe ore body.